"A powerful midwifery vision": Dutch student midwives' educational needs as advocates of physiological childbirth. Issue 6 (December 2019) - Thompson, Suzanne M.; Nieuwenhuijze, Marianne J.; Low, Lisa Kane; De Vries, Raymond
Abstract: Background: In order to internalize the midwifery philosophy of care and to learn how to advocate for physiological childbirth, student midwives in the Netherlands need learning experiences that expose them to physiological childbirth practices. Increased hospital births, wide variation in non-urgent referrals and escalating interventions impact on learning opportunities for physiological childbirth. Midwifery educators need to find ways to support student agency in becoming advocates of physiological childbirth. Objective: To gather students' opinions of what they need to become advocates of physiological childbirth. Methods: Focus groups with student midwives (n = 37), examining attitudes regarding what educational programs must do to support physiological childbirth advocacy. Results: Students reported feelings of personal power when the midwifery philosophy of care is internalized and expressed in practice. Students also identified dilemmas associated with supporting woman-centered care and promoting physiological childbirth. Perceived hierarchy in clinical settings causes difficulties, leading students to practice in accordance with the norms of midwife preceptors. Students are supported in the internalization and realization of the midwifery philosophy of care, including physiological childbirth, if they are exposed to positive examples of care in practice and have opportunities to discuss and reflect on these in the classroom. Key conclusion: Midwifery education should focus on strategies that include navigating dilemmas in practice and helping students to express the midwifery philosophy of care in communication with other professionals and with women. Preceptors need to be supported in allowing student midwives opportunities to realize the midwifery philosophy of care, also when this differs from preceptor practice.